Different Surgical Approaches for Multiple Fractured Atrophic Mandibles - Pereira, Felipe Ladeira (Thieme Medical Publishers, 2011)
Atrophic edentulous mandible fractures in geriatric patients have low incidence but present several biological and biomechanical peculiarities that produce a nonunion rate of around 20%. Surgical extraoral approaches for internal fixation of these fractures can be transcervical or by one or two submandibular incisions. Two patients sustaining multiple fractures in atrophic edentulous mandible are presented: the first patient was 72-years-old, treated by two submandibular incisions, and the second was 81-years-old, treated by transcervical approach. We discuss the advantages and drawbacks of each approach and their indications according to the Luhr et al (1996) atrophy index.